2022
DOI: 10.3390/s22030972
|View full text |Cite
|
Sign up to set email alerts
|

MXene Heterostructures as Perspective Materials for Gas Sensing Applications

Abstract: This paper provides a summary of the recent developments with promising 2D MXene-related materials and gives an outlook for further research on gas sensor applications. The current synthesis routes that are provided in the literature are summarized, and the main properties of MXene compounds have been highlighted. Particular attention has been paid to safe and non-hazardous synthesis approaches for MXene production as 2D materials. The work so far on sensing properties of pure MXenes and MXene-based heterostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 128 publications
(162 reference statements)
0
16
0
Order By: Relevance
“…These characteristics make it a promising candidate in diverse hightechnology applications, such as the electrodes of supercapacitors and as a sensing layer for gas sensors. 21,22 However, most common synthesis method for MXenes involve etching of the MAX phase via highly concentrated hydrofluoric acid, which, in addition to being highly toxic, generally leads to a high content of -F termination groups on the surface of the material, thus negatively affecting the performance of the supercapacitors. 23 All this limits the scaled-up large-scale, real-world applications of MXene.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make it a promising candidate in diverse hightechnology applications, such as the electrodes of supercapacitors and as a sensing layer for gas sensors. 21,22 However, most common synthesis method for MXenes involve etching of the MAX phase via highly concentrated hydrofluoric acid, which, in addition to being highly toxic, generally leads to a high content of -F termination groups on the surface of the material, thus negatively affecting the performance of the supercapacitors. 23 All this limits the scaled-up large-scale, real-world applications of MXene.…”
Section: Introductionmentioning
confidence: 99%
“…21 The advantageous attributes such as high metallic and semi-conductivity, rich chemistries, unique 2D morphologies, high surface area, and excellent flexibility make MXene potentially attractive for a variety of applications, such as in the development of gas sensors. 22 Among various MXenes discovered, Ti 3 C 2 T x (T x = −OH, −F, or −O) is one of the MXenes that are being widely studied for the detection of various VOCs and toxic gases until now. 23 It has been reported that Ti 3 C 2 T x MXene-based gas sensors have shown better sensitivity to VOCs over oxidizing gases.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are many research papers on MXenes, the key aspects have been summarized in informative review articles and books . In addition, a few overviews of MXene-based gas sensors have been reported. , However, no comprehensive review has focused on recent developments in the MXene gas sensors for potential applications. This review systematically describes the summary of a diverse range of MXenes and their synthesis methods.…”
mentioning
confidence: 99%